Characteristics of Quality of Life of Children with Cancer in RSAB Harapan Kita Jakarta - Mira Asmirajanti; Anita Sukarno; Sari, Widia; Pamungkas, Rian Adi; Pamungkas, Fhasa Lifiansah Azzah (Alta Dharma Publisher, 2022)
Background: Cancer is a common health burden among children. Uncontrolled metastases of cancer cells produce various clinical manifestations in children that impact their quality of life. Objective: This study aims to determine the description of the quality of life which includes physical function, emotional function, social function, and school function in children with cancer undergoing treatment at RSAB Harapan Kita Jakarta. Method: This cohort study was conducted among 28 inpatient cancer children in RSAB Harapan Kita Jakarta. PedsQol 4.0 was used to assess the quality of life level among children in 7 days of follow-up during their hospital stay. We assessed the mean differences in 7 days follow-up using Repeated Measure ANOVA. Result: This study found that the highest score of quality of life domain was on social function on the 5 day (mean= 19.57, SD=1.069) and the lowest score was on school function (mean=13.57, SD=2.911). There were no significant differences in scores of quality of life domains including physical (p-value = 0.828) and emotional function (p-value = 0.081), whereas, only social (p-value= 0.002) and school function (p-value= 0.008) was significantly changed in day 7 follow-up. Conclusion: Nursing intervention improve quality of life among children with cancer was essential that may support children’s growth and development according their age. Recommendation: Nurse need to consider the component of quality of life in providing the management among children with cancer